If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(7x + -1) = 3(2x + -1) + -4(x + 6) Reorder the terms: 4(-1 + 7x) = 3(2x + -1) + -4(x + 6) (-1 * 4 + 7x * 4) = 3(2x + -1) + -4(x + 6) (-4 + 28x) = 3(2x + -1) + -4(x + 6) Reorder the terms: -4 + 28x = 3(-1 + 2x) + -4(x + 6) -4 + 28x = (-1 * 3 + 2x * 3) + -4(x + 6) -4 + 28x = (-3 + 6x) + -4(x + 6) Reorder the terms: -4 + 28x = -3 + 6x + -4(6 + x) -4 + 28x = -3 + 6x + (6 * -4 + x * -4) -4 + 28x = -3 + 6x + (-24 + -4x) Reorder the terms: -4 + 28x = -3 + -24 + 6x + -4x Combine like terms: -3 + -24 = -27 -4 + 28x = -27 + 6x + -4x Combine like terms: 6x + -4x = 2x -4 + 28x = -27 + 2x Solving -4 + 28x = -27 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -4 + 28x + -2x = -27 + 2x + -2x Combine like terms: 28x + -2x = 26x -4 + 26x = -27 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 + 26x = -27 + 0 -4 + 26x = -27 Add '4' to each side of the equation. -4 + 4 + 26x = -27 + 4 Combine like terms: -4 + 4 = 0 0 + 26x = -27 + 4 26x = -27 + 4 Combine like terms: -27 + 4 = -23 26x = -23 Divide each side by '26'. x = -0.8846153846 Simplifying x = -0.8846153846
| (-2/5)3 | | w^2+16w+64=0 | | 5x+6=106 | | X^2=80X | | 4-3p=-2 | | 10v=60 | | 2(3-w)+6=-6(w-2)-7 | | 0(-8/7) | | X^2=34X | | -6/7w=-42 | | 4x^2-24x=-27 | | -8/15-23/25 | | 1/3(3x-9)=-10+6+3(2-x) | | 6(2x+1)=10x+4 | | 12x-10=10x-6 | | 0=4(-4x^2+10x-6) | | 3(x+14)=69 | | z^2+6z-27=0 | | -36=4v+4(v+7) | | 5/6*2/3=x | | -19/35+4/15 | | 3x^2+5=65 | | 9=3x-7 | | -120x+3000=-160x+4000 | | 7+2x=5x-5 | | 4x+2=32 | | 67-3x=9x+16 | | 7/9y+2+5/9y+6 | | 3a+2a=135 | | x-.3x=105 | | 4+8r-3=7r+29-3r | | 6z+18-9=27 |